2020
DOI: 10.1093/mnras/staa913
|View full text |Cite
|
Sign up to set email alerts
|

Interacting galaxies in the IllustrisTNG simulations - I: Triggered star formation in a cosmological context

Abstract: We use the IllustrisTNG cosmological hydrodynamical simulations to investigate how the specific star formation rates (sSFRs) of massive galaxies (M * > 10 10 M ) depend on the distance to their closest companions. We estimate sSFR enhancements by comparing with control samples that are matched in redshift, stellar mass, local density and isolation, and we restrict our analysis to pairs with stellar mass ratios of 0.1 to 10. At small separations (∼ 15 kpc), the mean sSFR is enhanced by a factor of 2.0 ± 0.1 in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 123 publications
(166 reference statements)
8
55
0
Order By: Relevance
“…Observations by Patton et al (2013) suggest that interaction-driven effects extend out to ∼150 kpc in projected separation. Patton et al (2020) confirm this effect in cosmological simulations, and demonstrate that close encounters affect galaxy pairs out to separations of ∼280 kpc in 3D space. Each interaction and flyby (Moreno 2012;Sinha & Holley-Bockelmann 2012;L'Huillier, Park & Kim 2015;) is capable of inciting bar formation (Łokas et al 2016;Pettitt & Wadsley 2018;Łokas 2019;Cavanagh & Bekki 2020) and promoting bulge mass growth (Just et al 2010;Bekki & Couch 2011).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Observations by Patton et al (2013) suggest that interaction-driven effects extend out to ∼150 kpc in projected separation. Patton et al (2020) confirm this effect in cosmological simulations, and demonstrate that close encounters affect galaxy pairs out to separations of ∼280 kpc in 3D space. Each interaction and flyby (Moreno 2012;Sinha & Holley-Bockelmann 2012;L'Huillier, Park & Kim 2015;) is capable of inciting bar formation (Łokas et al 2016;Pettitt & Wadsley 2018;Łokas 2019;Cavanagh & Bekki 2020) and promoting bulge mass growth (Just et al 2010;Bekki & Couch 2011).…”
supporting
confidence: 70%
“…Indeed, cosmological simulations (e.g. Perez et al 2006;Perez, Michel-Dansac & Tissera 2011;Bustamante et al 2018;Blumenthal et al 2020;Hani et al 2020b;Patton et al 2020) and zoom-in simulations (e.g. Sparre & Springel 2016) also provide a viable path.…”
mentioning
confidence: 99%
“…To date, there have been detailed investigations of the properties of merging galaxies at z = 0 − 1 in the Illus-trisTNG simulation. Patton et al (2020) found an enhancement in SFR at fixed mass in simulated merging systems in the IllustrisTNG simulations, which increases with decreasing pair separation, and agrees well with the observed SFR enhancements in low-redshift SDSS galaxies. The trend of increasing SFR at smaller scales becomes less pronounced as redshift increases from 0 to 1.…”
Section: Expectations From Simulationssupporting
confidence: 84%
“…With the advent of new observations of the starforming and chemical properties of merging pairs and morphologically-identified mergers at z ∼ 2, it will be important to extend the analysis of merging systems in cosmological simulations (e.g., Patton et al 2020) to higher redshift. The trend of declining enhancement in SFR at higher redshift over z = 0 − 1 in the IllustrisTNG simulation (Patton et al 2020) should be extended back to z ∼ 2. Such an analysis can be used to test the claims about the decreased effect of mergers on SFR at high redshift, based on the noncosmological simulations of Fensch et al (2017).…”
Section: Expectations From Simulationsmentioning
confidence: 99%
“…Although not similar work have been done using systems with two satellite galaxies, these results are consistent with those found by Lambas et al (2003); Alonso et al (2004); Patton et al (2013Patton et al ( , 2020 where the proximity between two paired galaxies triggers their star formation activity. In this sense, it is possible speculate that the tidal effects produced by the central galaxies in both satellites could strip them of their gas reservoir, and produce efficient bursts of star formation.…”
supporting
confidence: 86%